Solvent Effect on the Structural, Optical, Morphology, and Antimicrobial Activity of Silver Phosphate Microcrystals by Conventional Hydrothermal Method - Takeno, Mitsuo Lopes; Nobre, Francisco Xavier; da Costa, Fagner Ferreira; Botelho do Nascimento, Marcus Valério; Pessoa Júnior, Wanison André Gil; Araújo Júnior, Edgar Alves; Sousa, Giancarlo da Silva; de Sá, Marcel Leiner; Gurgel, Raiana Silveira; Albuquerque, Patrícia Melchionna; Matos, José Milton Elias de; Leyet Ruiz, Yurimiler; et al. (American Chemical Society (ACS), 2024)
The design of particle size and morphology are a promising approach to investigating the properties exhibited by different types of materials. In the present study, the silver phosphate microcrystals (Ag3PO4) were first time synthesized using the hydrothermal and solvothermal method by combination of the solvents water/isopropyl alcohol (SP-IA), water/acetone (SP-AC), water/ammonium hydroxide (AP-AH), all in a ratio of 1:1 (v/v). The synthesized materials were structurally characterized by X-ray diffraction (XRD), Rietveld refinement, and Raman vibrational spectroscopy, where it was confirmed that the pure phase was achieved for all prepared samples. The study of the optical properties by UV-vis diffuse reflectance spectroscopy (UV-vis/DRS) and colorimetry revealed that the obtained materials have an optical bandgap between 2.30 and 2.32 eV. The FE-SEM images collected revealed different morphologies for the synthesized materials, with a predominance of tetraploid-shaped microcrystals for the SP-AC sample, rods for the SP-IA sample, cubes and polyhedral for the SP-WT sample and condensed polyhedral for the SP-AH sample. The photocatalytic performance against the Rhodamine B dye (RhB) was 100%, 98.2%, 94.2%, and 87.8%, using the samples SP-AC, SP-IA, SP-WT, and SP-AH as photocatalyst at time of 12 min. On the other hand, the antimicrobial performance of SP-AC sample showed superior performance, resulting in the minimum inhibitory concentration─MIC of 7.81 μg mL-1 for the strain of E. coli, 7.81 μg mL-1 for the strain of E. aureus, 15.62 μg mL-1 for the strain of P. auruginosa, and 15.62 μg mL-1 for the strains of C. albicans. In this way, was synthesized a promissory antimicrobial and photocatalyst material, through an easy and cost-effective method.